Reward Weakened Inhibition of Return (IOR) in the Near Depth Plane. (February 2022) - Wang, Aijun; Lu, Feifei; Gao, Wenjing; Zhang, Tianyang; Zhang, Ming
In attentional orienting, researchers have proposed that reward history is a component of attentional control, as the reward value might enhance the spatial attention process to achieve more efficient goal-directed behavior and to improve target-detection performance. Although the effect of reward–induced motivation on attentional orienting has been studied in two–dimensional (2-D) space, the specific mechanisms underlying the influence of reward on inhibition of return (IOR) of attentional orienting in three-dimensional space (3-D) remain unclear. In the present study, by incorporating the Posner spatial-cueing paradigm into a virtual 3-D environment, we aimed to investigate the influence of reward on IOR in 3-D space. The results showed the following: (1) IOR size in the rewarded conditions was smaller than IOR size in the unrewarded condition in the near depth plane, resulting in an IOR difference with or without reward. (2) Reward weakened IOR in the near depth plane because the response to the uncued location was delayed, not because the response to the cued location was accelerated. The present study indicated that the different depth planes of the target location in 3-D space could influence the interaction between reward and IOR, and reward weakened IOR in the near depth plane.